Effect of the involvement degree of playing video games on brain waves for an hour - Lin, F L; Chang, C L; Jou, Y T; Pan, S C; Hsu, T Y; Huang, C D (2010 IEEE 17Th International Conference on Industrial Engineering and Engineering Management, 2010)
Subjects of this study are 12 persons divided into two even groups by the difference of involvement degree of playing video games. The subjects' brain waves of frontal lobe, parietal lobe, occipital lobe and temporal lobe are examined to find out how the subjects are affected after one hour of playing video games. The results show that α-waves and β-waves of the four lobes have no significant change. The percentages differences of relation between α-waves and β-waves are statistically significant. It was found that the α-waves of right frontal lobe are larger than those of the left frontal lobe in F3-F4. The reason of the opposing results may lie on the variable of playing time, that is, one hour of playing video games may be too short after all.